OFR 07-01, Till geochemical and indicator mineral reconnaissance of Minnesota - Thorleifson, L.Harvey; Harris, K.L.; Hobbs, H.C.; Jennings, C.E.; Knaeble, A.R.; Lively, R.S.; Lusardi, B.A.; Meyer, G.N. (Minnesota Geological Survey, 2007)
Maps and data from the <63 micron geochemical analyses of this study are also included in the MGS Open File Report OFR-09-02 As a cooperative project of the Minnesota Geological Survey and industry, the entire State of Minnesota and adjacent regions was sampled for till geochemistry and indicator minerals at a 30-km spacing during summer 2004. Within target cells, each a quarter-degree latitude by a half-degree longitude, till from between about 1 and 2 m depth was sampled by filling a 15 liter plastic pail. At a few sites, vertical profiles were collected. In addition, three transects to the north were sampled, to help identify sediments derived by long-distance glacial transport, to obtain reference samples from the Thompson nickel belt, and also to extend sampling to the limit of Hudson Bay-derived carbonate-bearing sediments, to permit comparison to Minnesota carbonate-bearing sediments. Three control samples anomalous in kimberlite indicator minerals from Kirkland Lake, Ontario, were also obtained. The resulting batch consisted of 250 samples covering Minnesota and adjacent areas, 20 samples from Canada, and the three standards. The results are a highly significant step forward in mapping our geochemical landscape, in clarifying mineral potential, in provision of reference data useful to environmental protection, public health, and exploration, and in supporting follow-up with respect to potential mineralization.